Influence of an unstable shoe on compensatory postural adjustments: An experimental evaluation - Andreia S. P. Sousa (2010)
This study attempted to evaluate the influence of using an unstable shoe in muscle recruitment strategies and center of pressure (CoP) displacement after the application of an external perturbation. Fourteen healthy female subjects participated in this study. The electromyographic activity of medial gastrocnemius, tibialis anterior, rectus femoris, biceps femoris, rectus abdominis and erector spinae muscles and the kinetic values to calculate the CoP were collected and analyzed after the application of an external perturbation with the subject in standing position, with no shoes and using unstable footwear. The results showed increased in medial gastrocnemius activity during the first compensatory postural adjustments and late compensatory postural adjustments when using an unstable shoe. There were no differences in standard deviation and maximum peak of anteroposterior displacement of CoP between measurements. From the experimental findings, one can conclude that the use of an unstable shoe leads to an increase in gastrocnemius activity with no increase in CoP displacement following an unexpected external perturbation.